Cloning, sequencing, and expression of isopropylbenzene degradation genes from Pseudomonas sp. strain JR1: identification of isopropylbenzene dioxygenase that mediates trichloroethene oxidation. - Pflugmacher, U (1996)
Pseudomonas sp. strain JR1, recently isolated with isopropylbenzene (IPB) as the inducer substrate for trichloroethene (TCE) oxidation (B. Dabrock, J. Riedel, J. Bertram, and G. Gottschalk, Arch. Microbiol 158:9-13, 1992), is able to degrade IPB via the meta-cleavage pathway. The genes encoding the first three enzymes in the catabolism of isopropylbenzene were isolated from a genomic library with the broad-host-range cosmid vector pWE15. A 7.6-kb fragment from a 37.7-kb primary cosmid clone was subcloned and sequenced. It contained seven complete open reading frames, designated ipbA1A2orf3A3A4BC. ipbA codes for the three subunits of a multicomponent IPB dioxygenase, ipbB codes for 2,3-dihydro-2,3-dihydroxy-IPB dehydrogenase, and ipbC codes for 3-isopropylcatechol 2,3-dioxygenase. The deduced amino acid sequences of ipbA1A2A3A4BC exhibited the highest homologies with the corresponding proteins of biphenyl-degradative pathways in gram-negative and gram-positive bacteria. The gene products of the ipb genes were identified by an in vitro transcription-translation system on the basis of their expected molecular masses. IPB dioxygenase and 3-isopropylcatechol 2,3-dioxygenase expressed in E. coli oxidized a wide range of alkyl aromatic compounds. Incubation of E. coli cells carrying ipbA1A2A3A4 with IPB and 10O2 yielded reaction products containing both atoms of molecular oxygen, which is in accordance with a dioxygenation reaction. E. coli recombinants harboring and expressing the IPB dioxygenase exhibited the ability to degrade TCE. The ipbA1A2A3A4-carrying E. coli strain required neither IPB nor isopropyl-beta-D-thiogalactopyranoside for induction; the rate of TCE degradation was comparable to that by fully induced Pseudomonas strain JR1.